The Manchurian candidate - Frankenheimer, John, 1930-2002; Axelrod, George, 1922-2003; Sinatra, Frank, 1915-1998; Harvey, Laurence, 1928-1973; Leigh, Janet; Lansbury, Angela, 1925-; Silva, Henry, 1928-; Gregory, James, 1911-2002; Condon, Richard (Europe : Metro Goldwyn Mayer, 2004)
A melodrama portraying the experiences of a man who has been brainwashed and trained to respond to hypnotic suggestion by the Communists during the Korean War and returned to the United States to assassinate a Senator.
Special features: Interview with Frank Sinatra, George Axelrod and John Frankenheimer; Feature-length audio commentary by director John Frankenheimer; Original theatrical trailer; Interactive moving menu screens and chapter selection.
Based on the novel of the same title by Richard Condon.
Originally released as a motion picture in 1962.
Frank Sinatra, Laurence Harvey, Janet Leigh, Angela Lansbury, Henry Silva, James Gregory.
BBFC: suitable only for persons of 15 years and over.
DVD; Region 2; Widescreen, aspect ratio 1.75:1; Dolby Digital.
English dubbed French, Italian or Spanish dialogue, with optional English, Dutch, French, Spanish, Portuguese, Swedish, Danish, Norwegian, Finnish, Polish, or Italian subtitles. English for the hearing impaired.
Keywords: Presidents -- Assassination attempts -- Drama; Feature films; Fiction films; Thrillers (Motion pictures)